(untitled) (Journal of Nonlinear Modeling and Analysis, 2025)
In this paper, using the Mountain Pass Theorem, we present results on compactness and the existence of solutions for a class of local and nonlocal p-Laplacian equations involving Robin boundary conditions, with critical nonlinearity and a small perturbation.